2020
DOI: 10.1177/1756286420902358
|View full text |Cite
|
Sign up to set email alerts
|

Personalized risk prediction of symptomatic intracerebral hemorrhage after stroke thrombolysis using a machine-learning model

Abstract: Background: Personalized prediction of the risk of symptomatic intracerebral hemorrhage (sICH) after stroke thrombolysis is clinically useful. Machine-learning-based modeling may provide the personalized prediction of the risk of sICH after stroke thrombolysis. Methods: We identified 2578 thrombolysis-treated ischemic stroke patients between January 2013 and December 2016 from a multicenter database, where 70% were used to train models and the remaining 30% were used as the nominal test sets. Another 136 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Wang et al studied the usefulness of ML algorithms to predict symptomatic ICH after thrombolysis in 2237 patients with hyperacute ischemic stroke [11]. Of these ML…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al studied the usefulness of ML algorithms to predict symptomatic ICH after thrombolysis in 2237 patients with hyperacute ischemic stroke [11]. Of these ML…”
Section: Discussionmentioning
confidence: 99%
“…However, the learning result of additional ANN models performed with the scaling input variable in our study were not better than the crude ANN model. In other DL studies relating to stroke, there was no mention of the effect of neural network scaling on DL performance [11,39]. Ahsan et al reported the effect of scaling on performance in various ML methods [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [20] have implemented a machine learning model in the configuration of the risk of symptomatic intracerebral hemorrhage (sICH) after the thrombolysis of the stroke. The risk factors of sICH are theoretically used after stroke thrombolysis.…”
Section: Related Workmentioning
confidence: 99%
“…Without using any follow-up data, the maximum achieved AUC = 0.92. Wang et al [21] employed logistic regression, ANN, SVM, random forest and AdaBoost for the prediction of symptomatic intracerebral hemorrhage (sICH) on 2237 samples. Oversampling and cost-sensitive adaptation was used for imbalanced distribution of sICH to no-sICH and achieved AUC = 0.82.…”
Section: Dichotomized Outputmentioning
confidence: 99%